PWE-331 Impact of the interval between long-course chemoradiotherapy and resection of locally-advanced rectal cancer upon mri down-staging – data from a pilot randomised controlled trial. (22nd June 2015) - Foster, J; Roach, H; Francis, N
Abstract : Introduction: The optimal time interval between chemoradiotherapy (CRT) and surgery for rectal cancer has not been clearly defined. A longer interval may facilitate greater tumour down-staging. There is, however a paucity of high-quality evidence, with the majority of published data being from observational studies. Method: This study explores down-staging of rectal cancer assessed by Magnetic Resonance Imaging (MRI) within a pilot Randomised Controlled Trial (RCT) comparing an interval of six weeks versus an interval of 12 weeks. Patients with rectal cancer requiring long-course CRT from seven sites were randomised to have surgery after an interval of either 6 weeks or 12 weeks following completion of long-course CRT. MRI scans were performed at baseline and at approximately 1 week prior to surgery. Additionally in the 12-week arm an additional "interval" MRI scan was performed approximately 5–6 weeks after completion of CRT. All scans were de-identified and analysed by a single blinded consultant gastrointestinal radiologist. Tumours were staged using the TNM system and the response to CRT by the tumour regression grade (TRG) system. Results: Fifteen patients were randomised to surgery at 6-weeks and 16 to surgery at 12-weeks. Six patients (40%) from the 6-week arm and seven (50%) from the 12-week arm showed down-staging of the primary tumour by 1 or more stage between baseline and pre-operative MRI scans. Lymph node down-staging was observed for 10 patients (67%) in the 6-week arm and nine patients (64%) in the 12-week arm. No patients had an increase in T stage, although two patients in the 6-week arm had an increase in N stage between baseline and 6 weeks. Three patients (21%) in the twelve week arm showed ongoing down-staging of T stage on MRI between 6 and 12-weeks, and four patients had a reduction of their TRG between scans, indicating ongoing down-staging. Conclusion: Although limited by small sample size, this analysis of data from a randomised controlled trial demonstrates that ongoing down-staging may continue between six and twelve weeks following completion of CRT. A longer interval might be considered where resection margins are still threatened on MRI at six weeks. Disclosure of interest: None Declared.